Fratries amies, fratries ennemies dans La Mariane de Tristan - Sandrine Berrégard (Etudes Epistémè)
This article deals with the dramatic role of brothers and sisters in La Mariane, especially the symbolic function attributed to them. The playwright sets up a direct confrontation between two groups of contradictory characters: on the one hand, the formidable triad of Hérode, Phérore and Salomé, on the other, the virtuous twin-like couple formed by Mariane and Aristobule, the distinctive trait of the latter being to appear exclusively under the form of a vengeful shadow. This analysis cannot, however, neglect a careful examination of the historical sources from which Tristan has drawn (principally the Antiquités judaïques of Flavius Joseph and La Cour sainte of Caussin) as well as the theatrical model afforded to him by Hardy’s Mariamne. The comparison with these hypotexts reveals the increased importance of siblings in La Mariane. The protagonists belong to a still larger family composed of analogous figures, such as the Virgin Mary whose memory is revived by the final assumption of the tragic heroine who appears alongside other martyrs in Tristan’s L’Office de la sainte Vierge. The author employs the sisterly metaphor to evoke the relationship of La Mariane to his second play, Panthée, as if to underline the operative value of the functions it implies.